Mother’s Commitment to Limiting Screen Time among Preschool-Aged Children and Its Influencing Factors - Diana Rachmania; Dhina Widayati; Madiha Mukhtar (Jurnal Ilmiah Kesehatan, 2026)
Excessive use of gadgets has a negative impact on children's health and development. Mothers' commitment to limiting screen time is key to preventing children from the negative impacts of gadget use. This study aims to analyze factors related to mothers' commitment to limiting screen time in preschool-aged children. The research design used was a correlational study. The sample in this study were 60 mothers with preschool children with a total sampling technique. The research variables were mothers' commitment to limiting screen time and factors such as age, education, occupation, number of children, mother's motivation, husband's support, and residential environment. The research instrument was a questionnaire. Data were analyzed using the Chi-Square statistical test. The results showed that almost all mothers (85%) had sufficient commitment to limiting screen time. The results of data analysis with a significance of α <0.05 showed that education, occupation, motivation, and residential environment were related to mothers' commitment to limiting screen time in children, while age, number of children, and husband's support were not related. Mothers are expected to actively adjust strategies for limiting screen time for their children while still providing active support when with their children